Analysis of the problem of monitoring the development of healthimproving physical activity of future physical education teachers - Sokolyuk, O. V. (Problems of Engineer-Pedagogical Education, 2018)
The article considers and analyzes the definitions of the term "health-improving motor activity" given by different scientists. By means of carrying out an analysis the difference between the concepts of monitoring physical development and monitoring motor activity has been studied. The main aspects of monitoring the development of health-improving motor activity (HIMA) of future physical education teachers are analyzed. The definition of "monitoring of the development of health-improving motor activity" is given. The degree of the importance of HIMA is defined. The author has come to the conclusion that monitoring of the development of healthimproving motor activity of future physical education teachers is a scientifically substantiated, continuous, diagnostic and prognostic comprehensive system of gathering, storing, analyzing and disseminating information on physical development and its role in the professional training of future physical education teachers on the basis of their conformity with the identified goals and expected outcomes (integrated tracking of their development in accordance with all the indicators of professional training).